The Transformative Power of Knowledge Sharing in Settings of Poverty and Social Inequality. Issue 11 (November 2018) - Qureshi, Israr; Sutter, Christopher; Bhatt, Babita
Knowledge sharing is central to reducing inequality and alleviating poverty. However, communities in settings of extreme poverty are often bounded by distinct perspectives and understandings that hinder knowledge sharing. Furthermore, social fault lines may create internal boundaries that impede interaction, further complicating knowledge sharing. Despite these challenges, some knowledge sharing efforts are successful. The purpose of this study is to better understand how knowledge sharing overcomes boundaries in settings of extreme inequality and poverty. Using qualitative data from rural India, we find that boundary work performed by boundary spanners overcomes external and internal boundaries by creating space for action, observation, and reflection in the recipient community. These actions, or syncretizing mechanisms, transform newly introduced knowledge, which then facilitates further boundary work, resulting in community transformation. Under certain circumstances, we see how boundary work and syncretism can lead to significant knowledge and recipient transformation. Thus, we seek to contribute to the literature by more fully exploring the transformative power of knowledge sharing within contexts of extreme poverty, and by explaining the process by which it occurs.